Cinnamaldehyde-based poly(thioacetal): A ROS-awakened self-amplifying degradable polymer for enhanced cancer immunotherapy. (October 2022) - Tu, Yalan; Xiao, Xuan; Dong, Yansong; Li, Jisi; Liu, Ye; Zong, Qingyu; Yuan, Youyong
Abstract: Although stimuli-responsive polymers have emerged as promising strategies for intelligent cancer therapy, limited polymer degradation and insufficient drug release remain a challenge. Here, we report a novel reactive oxygen species (ROS)-awakened self-amplifying degradable cinnamaldehyde (CA)-based poly(thioacetal) polymer. The polymer consists of ROS responsive thioacetal (TA) group and CA as the ROS generation agent. The self-amplified polymer degradation process is triggered by endogenous ROS-induced cleavage of the TA group to release CA. The CA released then promotes the generation of more ROS through mitochondrial dysfunction, resulting in amplified polymer degradation. More importantly, poly(thioacetal) itself can trigger immunogenic cell death (ICD) of the tumor cells and its side chains can be conjugated with indoleamine 2, 3-dioxygenase 1 (IDO-1) inhibitor to reverse the immunosuppressive tumor microenvironment for synergistic cancer immunotherapy. The self-amplified degradable poly(thioacetal) developed in this work provides insights into the development of novel stimulus-responsive polymers for enhanced cancer immunotherapy.